Design of an Eddy Current Testing System for Non-Magnetic Hollow Tube Inspection - Yasmine Belkahla; Ghalem Hadri Khoussa; Abdelhalim Taieb brahimi; Nabil Boughanemi (e-Journal of Nondestructive Testing)
This paper presents an experimental setup for Eddy Current Non-Destructive Testing of non-magnetic hollow tubes. The system